2020
DOI: 10.3390/cancers12071883
|View full text |Cite
|
Sign up to set email alerts
|

Fast, In Vivo Model for Drug-Response Prediction in Patients with B-Cell Precursor Acute Lymphoblastic Leukemia

Abstract: Only half of patients with relapsed B-cell precursor (BCP) acute lymphoblastic leukemia (ALL) currently survive with standard treatment protocols. Predicting individual patient responses to defined drugs prior to application would help therapy stratification and could improve survival. With the purpose to aid personalized targeted treatment approaches, we developed a human–zebrafish xenograft (ALL-ZeFiX) assay to predict drug response in a patient in 5 days. Leukemia blast cells were pericardially engrafted in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Our findings concur with similar observations made in a preclinical model of AML. 20 To validate this synergistic interaction in vivo, we used an established xenograft model in zebrafish embryos 21 , where BCP-ALL cells (SEM) are injected into the pericardium of immunosuppressed zebrafish embryos and bathed in the drug for 72h before flow cytometrically evaluating effects on BCP-ALL cells. Analyses showed an enhanced induction of apoptosis (p<0.05) after combined silmitasertib/venetoclax treatment (Figure 2F) and confirmed silmitasertib induced downregulation of MCL1 as functional underpinning of the synergistic treatment effect also in vivo (Supplementary Figure S10).…”
mentioning
confidence: 99%
“…Our findings concur with similar observations made in a preclinical model of AML. 20 To validate this synergistic interaction in vivo, we used an established xenograft model in zebrafish embryos 21 , where BCP-ALL cells (SEM) are injected into the pericardium of immunosuppressed zebrafish embryos and bathed in the drug for 72h before flow cytometrically evaluating effects on BCP-ALL cells. Analyses showed an enhanced induction of apoptosis (p<0.05) after combined silmitasertib/venetoclax treatment (Figure 2F) and confirmed silmitasertib induced downregulation of MCL1 as functional underpinning of the synergistic treatment effect also in vivo (Supplementary Figure S10).…”
mentioning
confidence: 99%
“…Site of cancer cell implantation. One of the most important factors affecting engraftment potential is the site of cell implantation [32]. The yolk sac has traditionally been the most employed location because it provides a larger site for housing transplanted cells [10] (Supplementary Table S1); however, we herein demonstrated the yolk to be the worst site for implantation, as it had the lowest rates of survival, tumor engraftment and growth.…”
Section: Discussionmentioning
confidence: 69%
“…VEN in vitro incubation of KMT2A -r cell lines SEM and RS4;11 with low nanomolar and physiologically achievable concentrations resulted in severely reduced tumor cell counts, apoptosis induction, and morphological changes. Other groups conducting basic viability screenings with the same cell lines achieved comparable results [ 5 , 14 , 22 , 23 ]. In vivo application of VEN induced decelerated tumor cell growth rates and reduced blast frequencies in bone marrow and spleen in both KMT2A -r cell line-derived xenograft systems.…”
Section: Discussionmentioning
confidence: 82%
“…In vivo application of VEN induced decelerated tumor cell growth rates and reduced blast frequencies in bone marrow and spleen in both KMT2A -r cell line-derived xenograft systems. Gauert et al used SEM cells in a zebrafish xenograft model and found comparable results [ 23 ]. The fact that mice engrafted with RS4;11 cells, which were highly responsive to VEN incubation in vitro, seemed to benefit less from VEN therapy than SEM-derived models, is most likely due to the faster proliferation kinetics of SEM cells compared to RS4;11.…”
Section: Discussionmentioning
confidence: 99%